Analisis Faktor Dalam Pencegahan Penyebab Kematian Ibu Di Kabupaten Mamuju - Thalib, Kiki Uniatri; D, Yuliana; Sallo, Andi Kamal M.; Darmansyah, Safriadi; Rabuana, Susi; Susanti, Susanti; Parwati, Dewi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Promotion is one part of a series of marketing activities for a good/service. Promotion is not only a communication tool between companies and consumers, but is also a tool to influence consumers in purchasing activities or using services according to their desires and needs. This research aims to determine the influence of men's clinic promotions on people's enthusiasm for carrying out health checks. The research method used is a qualitative method with unpatterned research. Because it is patterned, you can use this design to help in research. From the research results, it can be concluded that the current health problem in Indonesia is that millennials still have low awareness about using social media as a health promotion tool. The author gives a suggestion that in the future it is hoped that in the future the clinic will further increase the promotions that have been carried out so that the public is more aware of men's clinics and the public is more aware of the dangers of male reproductive health and how to overcome them.